(3GdQSGdI GdaJMjI aj CYeGd GdLjHjIs - (3GdOeTbqj GdeGpQOjfj, SHW GdeGQOjfj, HOQ GdOjf (B- (3GdZRGd, eMeO Hf eMeO Hf CMeO, (B912 (3g`s ((3YKeGf Hf eMeOs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO agPg QSGdI aj GdYed HGdQY GdeLjH eTJedI Ydi ebOeI hYTQjf HGHG hNGJeI SejJgG HGdQSGdI GdaJMjI aj CYeGd GdLjHjIs
(3BNQgG (B:s
(3eWGdYI ef eWGdY GdTQhb GdeSJbjd Hbj GdHGbj ef Gddjd YfO JhSWg hCf SGhi MUJg GdaLQ JhSW Chd hbJ GdaLQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 2 / 624s
(3gOjI GdYGQajf(B: 2 / 218s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3gjFIs